PENGUATAN KARAKTER INTEGRITAS SISWA OLEH GURU PKn SEBAGAI UPAYA PENCEGAHAN BULLYING DI SMA NEGERI 1 MORONGE KABUPATEN KEPULAUAN TALAUD - Theodorus Pangalila; Sjamsi Pasandaran; Anace Carolina Essing (Labor Program Studi Pendidikan Sosiologi, 2022)
This study aims to get an overview of the strengthening of the character of integrity in SMA N 1 Moronge, where the strengthening of the character of integrity in the school environment and outside the school environment has differences. So what happens is that there are still some students who have not applied the character of integrity that exists in these students. Such as still violating school rules, not respecting the differences between fellow friends, acting rudely to both friends and teachers and not respecting every direction given by the teacher. The method used in this research is a qualitative research method with a descriptive approach, with data collection techniques through observation, interviews, and documentation with school principals, Civics subject teachers and students in the Moronge 1 State High School environment. Based on the results of research conducted by researchers, it has been seen that the principal and Civics subject teachers have made various efforts to strengthen the character of integrity to students in the school environment. Namely by providing guidance, direction, and approaches to students so that students have good character or attitude